Quality of ultra-high temperature treated chocolate milk manufactured in Bangladesh (Bangladesh Journal of Animal Science, 2015)
Quality of ultra-high temperature (UHT) treated chocolate milk manufactured by different manufacturing companies of Bangladesh was evaluated. The milk samples were collected from retail shops of different markets supplied by three major dairy brands namely Aarong, Starship and Milkman. From the organoleptic tests it was found that there were no significant variation in consistency, but significant variations (p?0.05) were found in case of flavor and colour and appearance, pH and solids-not-fat (SNF) content showed insignificant difference, while significant variations at different levels (p